A Rare Ultra-Long-Term Complication of Occluder Recanalization Due to Spontaneous Perforation of Polyvinyl Alcohol Membrane of Atrial Septal Defect Occluder: A Case Report and Review of the Literature - Xiang, Kun; Zhuang, Huanwei; Wu, Qin; Tang, Mi; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2022)
Percutaneous closure of atrial septal defect (ASD) has emerged as a feasible alternative strategy to surgical repair in many cardiac centers worldwide. Occluder recanalization due to device failure is a rare and severe complication that often occurs within weeks to years after ASD closure. We reported a rare ultra-long-term complication of occluder recanalization due to delayed spontaneous perforation of polyvinyl alcohol (PVA) membrane of ASD occluder after 18 years of ASD closure. Surgical removal of the faulty device and reconstruction of the atrial septum with a bovine pericardial patch was performed. The patient was discharged and recovered uneventfully without syncope or residual shunt. The cause of this rare complication of spontaneous PVA membrane perforation of the occluder has not been fully detected. To our knowledge, this is the first report about PVA membrane perforation of an occluder that occurred soon after ASD closure.